Pulmonary sarcoidosis is associated with exosomal vitamin D-binding protein and inflammatory molecules - Maria-Jose Martinez-Bravo; Casper J.E. Wahlund; Khaleda Rahman Qazi; Robert Moulder; Ana Lukic; Olof Rådmark; Riitta Lahesmaa; Johan Grunewald; Anders Eklund; Susanne Gabrielsson (Elsevier, 2022)
BACKGROUND: Sarcoidosis is an inflammatory granulomatous disorder characterized by accumulation of TH1-type CD4+T cells and immune effector cells within affected organs, most frequently the lungs. Exosomes are extracellular vesicles conveying intercellular communication with possible diagnostic and therapeutic applications.
OBJECTIVES: Weaimed to provide an understanding of the proinflammatory role of bronchoalveolar lavage fluid (BALF) exosomes in patients with sarcoidosis and to find candidates for disease biomarkers.
METHODS: Weperformed a mass spectrometric proteomics characterization of BALF exosomes from 15 patients with sarcoidosis and 5 healthy control subjects and verified the most interesting results with flow cytometry, ELISA, and Western blot analyses in an additional 39 patients and 22 control subjects.
RESULTS: Morethan 690 proteins were identified in the BALF exosomes, several of which displayed significant upregulation in patients, including inflammation-associated proteins, such as leukotriene A4 hydrolase. Most of the complement-activating factors were upregulated, whereas the complement regulator CD55 was seen less in patients comparedwith healthy control subjects. In addition, for the first time, we detected vitamin D-binding protein in BALF exosomes, which was more abundant in patients. To evaluate exosome-associated vitamin D-binding protein as a biomarker for sarcoidosis, we investigated plasma exosomes from 23 patients and 11 healthy control subjects and found significantlyhigher expression in patients.
CONCLUSION: Together,these data contribute to understanding the role of exosomes in lung disease and provide suggestions for highly warranted sarcoidosis biomarkers. Furthermore, the validation of an exosome-associated biomarker in the blood of patients provides novel, and less invasive, opportunities for disease diagnosis.